2020
DOI: 10.3389/fcimb.2020.601834
|View full text |Cite
|
Sign up to set email alerts
|

Urban Life as Risk Factor for Aspergillosis

Abstract: Aspergillus fumigatus (Af) frequently colonizes the airways of patients with cystic fibrosis (CF) and can cause severe diseases, such as allergic bronchopulmonary aspergillosis, Af bronchitis or even Af pneumonia. However, risk factors, including environmental factors, for acquiring Af in the respiratory tract of patients with CF are rarely studied and described. The aim of this study was to investigate whether urban or rural life could affect colonization with Af in the respiratory tract of patients with CF. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Aspergillosis likely is more frequently diagnosed in higher income patients because of their ability to continually seek treatment for associated risk factors. Income differences also could relate to cost of living because aspergillosis is more likely to be diagnosed in urban than rural patients (32).…”
Section: Discussionmentioning
confidence: 99%
“…Aspergillosis likely is more frequently diagnosed in higher income patients because of their ability to continually seek treatment for associated risk factors. Income differences also could relate to cost of living because aspergillosis is more likely to be diagnosed in urban than rural patients (32).…”
Section: Discussionmentioning
confidence: 99%
“…All these risk factors should be taken into account during exacerbations of the disease, especially when laboratory tests confirm colonization, and there is no response after administration of appropriate medications. 6,67,[73][74][75] Implementation of highly effective CFTR modulators during the last few years has been a breakthrough in CF care. However, the chronic inflammation and infection with bacteria and fungi in the CF airways are still outstanding challenges.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…67 68 69 Two more recent studies reported an age of acquisition being 16.4 years in the United States, 13.5 years in France, and 9.0 years in the United Kingdom. 66 67 68 69 70 71 72 73 Two other studies have broken down the prevalence of A. fumigatus colonization into different age categories showing colonization rates of 16.4% up to 28% in children <12 years of age. By differentiating transient (≤1/year) from persistent (≥2/year) colonization, Saunders et al showed that children <12 years of age were only transiently colonized in a minority of the cases (21%), with the majority of children ≥12 years (59%) being persistently colonized with Aspergillus .…”
Section: Pathogenesis Of Aspergillus Spp Colonization...mentioning
confidence: 99%
See 1 more Smart Citation
“…Aspergillus fumigatus frequently colonizes the airways of patients with cystic fibrosis and can cause severe disease such as allergic bronchopulmonary aspergillosis, A. fumigatus bronchitis, or even A. fumigatus pneumonia. Urban living should be considered as a possible new risk factor for A. fumigatus colonization of the airways of cystic fibrosis patients [ 47 ].…”
Section: Difference Of Sex and Gender Of The Human Host In Susceptibi...mentioning
confidence: 99%